An Unusual Foreign Body in a Child’s Airway - a Metallic Spark Wheel of a Gas Lighter - Tahura, Sarabon; Talukder, Diti; Akter, Johora; Chakraborty, Biswajit; Anowar, Asma Bint (Northern International Medical College Journal, 2025)
Foreign body aspiration (FBA) is a common pediatric emergency, particularly in children under 5 years. While organic materials such as nuts and seeds are most frequently aspirated, metallic foreign bodies are comparatively less common and can present distinctive therapeutic challenges. We report a 4-year-old boy who presented with persistent cough and respiratory distress following an unwitnessed aspiration. Chest radiography revealed a radio-opaque well-defined object near the carina. Flexible bronchoscopy identified a metallic spark wheel from a gas lighter lodged just above the carina, slightly deviated toward the right main bronchus. Retrieval was technically challenging due to its large size and smooth central projection but was successfully performed using rat-tooth forceps via flexible bronchoscope. The child recovered without complications. Metallic foreign bodies, though uncommon, are frequently reported in children. However, to our knowledge, this is the first case of a gas lighter spark wheel aspiration. Its unique design posed specific technical challenges during retrieval, highlighting the importance of pre-procedural planning, tool selection, and operator expertise. Flexible bronchoscopy proved to be an effective and safe method for managing this unusual foreign body. Northern International Medical College Journal Vol. 15 No. 1-2 July 2023-January 2024, Page 695-697